Pemberian Edukasi Perilaku Hidup Bersih Dan Sehat Pada Anak-Anak Di Desa Uwemanje Kecamatan Kinovaro - Devi Fanesa Pakaya; Yelci Kaloan; Annisa Pagotja; Sry Devi; Mutiara Annisa S.Hi. Ukum; Ni Kadek Maharani; Ni Kadek Wiranti; Nursinta Handayani; Nurul Fajria; Renaldy; Risqa Amalia; Rivaldi Nardi; Rosmita Sahran; Katrina Feby Lestari (AMMA : Jurnal Pengabdian Masyarakat, 2022)
COVID-19 is a disease that attacks the respiratory system in humans. This virus has infected millions of people, causing high mortality rates for sufferers worldwide. Children are a group that is very vulnerable to the transmission of COVID-19. Therefore, PHBS is an alternative to help prevent the transmission of COVID-19. PHBS is very important to do early on because in addition to helping individuals avoid the transmission of COVID-19, it is also to prepare the younger generation to be aware of their own health and the environment. The purpose of this community service activity is to educate children regarding PHBS during the COVID-19 pandemic. The target of this activity is the children of the 5th Corps Salvation Army Church, Uwemanje Village, Kinovaro District. The location of this activity was carried out at the Church of the 5th Corps Salvation Army, Uwemanje Village, Kinovaro District. This activity was carried out with 2 methods, namely the presentation of PHBS material as well as a demonstration of washing hands with soap. The results of the activity showed that the children already had general knowledge about PHBS, seemed enthusiastic about listening and participated in practicing hand washing with soap properly. We hope that the children in Uwemanje Village can always practice PHBS in their daily lives. Keywords: Education, PHBS, Children